Refreshing Experience: The Christ-Event as Fact, Classic, and Phenomenon - Kelly, Anthony (Irish theological quarterly, 2012)
This article accepts that theology is always in danger of becoming abstract and losing its distinctive sense of reality. Part of the problem is the way a critical theology can become removed from experience. A constructive response to this problem—of special relevance to theological education and pastoral communication—is fostering an interplay in Christian experience between the empirical ‘fact’ of Christianity, the ‘classic’ form of Christian revelation, and ‘the phenomenon’ of God’s self-revelation experienced in the corporate consciousness of the Church.